1984
DOI: 10.1002/ajmg.1320180315
|View full text |Cite
|
Sign up to set email alerts
|

Familial neonatal and infantile seizures: An autosomal‐dominant disorder

Abstract: Familial neonatal seizures are an important and probably underrecognized disorder. A family with six affected individuals in three generations was evaluated and their clinical characteristics were compared with those of 15 families previously reported in the literature. An analysis of the 116 affected individuals uncovered a typical clinical picture of onset of seizures by 2 to 8 days of life in an otherwise healthy appearing infant, and cessation of seizures by 1 to 6 months. Results of diagnostic evaluations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Consistent with prior cases of R448X (5), none of our patients have experienced seizures outside of infancy. Interestingly, the KCNQ2 C-terminal truncation mutant R448X has been shown to reduce the potassium current by <50% and to cause no changes in the ion channel's biophysical properties (6).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with prior cases of R448X (5), none of our patients have experienced seizures outside of infancy. Interestingly, the KCNQ2 C-terminal truncation mutant R448X has been shown to reduce the potassium current by <50% and to cause no changes in the ion channel's biophysical properties (6).…”
Section: Discussionsupporting
confidence: 91%
“…In our case, the family history given by the grandmother of the proband was key to the diagnosis, and further genetic study identified a putative causative mutation in KCNQ2, the R448X (5, 6). Consistent with prior cases of R448X (5), none of our patients have experienced seizures outside of infancy.…”
Section: Discussionmentioning
confidence: 74%
“…Newborn infants with cerebral dysgenesis and neurocutaneous disorders such as incontinenti pigmenti or organoid nevus syndrome (Clancy et al, 1985~) may have unprovoked epileptic seizures. Similarly, in "benign neonatal seizures," (Plouin, 1985), familial neonatal seizures (Zonana et al, 1984) and, according to French authors "fifth-day fits" (Navalet et al, 1981), spontaneous clinicalEEG seizures may arise unexpectedly, sometimes followed by more typical forms of epilepsy in later life. These are uncommon causes of neonatal seizures, however.…”
Section: Discussionmentioning
confidence: 99%
“…Most seizures resolve completely by 6 months of age, but the pattern is not completely benign, with 10 to 14% developing later epilepsy. 5,6 Leppert et al 7 linked benign familial neonatal convulsions to the CMM6 and RMR6 regions on chromosome 20q. Linkage analysis from a multiplexed family containing 19 people with benign familial neonatal convulsions showed localization at two DNA regions on chromosome 20q, 7,8 but a locus on chromosome 8q was found in one family.…”
Section: Idiopathic Generalized Epilepsymentioning
confidence: 99%